The Coexistence of Local and Global Food Supply Chains: The Lombardy Region Case Study - Chiara Mazzocchi; Stefano Corsi; Giordano Ruggeri (Agriculture, 2020)
Over the last years, the trust of consumers in the quality and sustainability of the food system has weakened due to the disconnection between producers and consumers. Alternative Food Networks (AFNs) and Short Food Supply Chains (SFSCs), born out of the perceived loss of trust in the globalized food system, are trying to shorten the gap between farmers and consumers. Nowadays, many scholars agree that local and global food systems coexist, and consumers usually buy both in local and in global food chains. Our study aims to understand the factors that affect the development of AFNs with a specific focus on the interactions with small- and large-scale food retailing in the Lombardy region in the north of Italy. We employ an Ordinary Least Square (OLS) model, on a municipal scale, in which the dependent variable measures the number of participatory activities carried out by farmers and consumers in AFNs. The main results highlight that conventional large retailers and alternative food networks are linked, and that the coexistence of the two market channels may lead to the development for both of them. Contrarily, where small stores exist, they may compete with an alternative food channel, as they offer similar products and services.